2020
DOI: 10.1371/journal.pone.0236359
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer: Clinicopathological features and associated risk factors in a high risk population presenting to a major tertiary care center in Pakistan

Abstract: Oral squamous cell carcinoma (OSCC) has the highest prevalence in head and neck cancers and is the first and second most common cancer in males and females of Pakistan respectively. Major risk factors include peculiar chewing habits like areca nut, betel quid, and tobacco. The majority of OSCC presents at an advanced stage with poor prognosis. On the face of such a high burden of this preventable cancer, there is a relative lack of recent robust data and its association with known risk factors from Pakistan. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 48 publications
(58 reference statements)
4
33
0
Order By: Relevance
“…For example, it has been observed that males, particularly those with a lower socioeconomic status, consume more tobacco products compared to females. 10 The various forms of tobacco used in Karachi include (i) smoking, such as cigarettes, bidi (dried and rolled tobacco leaves), shisha (tobacco with fragrant liquid) and, (ii) chewing smokeless tobacco including paan (betel-quids), beetle-nuts, naswar (powdered moist tobacco which is kept in the base of oral cavity or alongside teeth between the cheek and mandible for a long time), and gutka (a mixture of paraffin wax, areca nuts, lime, catechu, and tobacco). In Karachi, the use of smokeless tobacco ( naswar and gutka ) is particularly high compared to other parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been observed that males, particularly those with a lower socioeconomic status, consume more tobacco products compared to females. 10 The various forms of tobacco used in Karachi include (i) smoking, such as cigarettes, bidi (dried and rolled tobacco leaves), shisha (tobacco with fragrant liquid) and, (ii) chewing smokeless tobacco including paan (betel-quids), beetle-nuts, naswar (powdered moist tobacco which is kept in the base of oral cavity or alongside teeth between the cheek and mandible for a long time), and gutka (a mixture of paraffin wax, areca nuts, lime, catechu, and tobacco). In Karachi, the use of smokeless tobacco ( naswar and gutka ) is particularly high compared to other parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by earlier exposure to common risk factors such as tobacco use [7] as is the case in India or Pakistan. In these regions, the average age of patients is between 41 and 50 years and one-third of the population aged 15 years uses tobacco in any form [22]. However, the consumption of these substances (tobacco and alcohol) is not common among patients with OCC in Senegal [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The tongue is one of the most common sites in OCCs with 40% of cases [8] especially in Western countries due to excessive smoking and alcohol consumption [22]. In 2005, according to Touré et al [10], the mandible (24.8%), tongue (21.9%) and maxilla (15.2%) represented the majority sites.…”
Section: Discussionmentioning
confidence: 99%
“…The South Asian countries were observed to have significantly higher incidence rates of OSCC. Among them, India has the largest number of cases globally (one-third), while in Pakistan, it is the first and second most prevalent cancer in males and females, respectively [4]. The risk factors include use of alcohol and tobacco, poor oral hygiene, exposure to human papillomavirus (HPV), genetic background, lifestyle, ethnicity, and geographical location.…”
Section: Introductionmentioning
confidence: 99%